EDUCATIONAL-SCIENTIFIC PROGRAM BY SPECIALTY 224 "TECHNOLOGIES OF MEDICAL DIAGNOSIS AND TREATMENT" - Mintser, O. P.; Babkina, T. M.; Shcherbina, O. V.; Klymenko, S. V.; Krasnov, V. V.; Korol, P. O.; Sergiienko, L. I. (Medical Informatics and Engineering, 2023)
Background. The development of the health care industry is impossible without the use of modern technologies, which have recently become one of the decisive factors for ensuring high-quality and effective medical diagnosis and treatment of patients. Due to the involvement of information and communication and digital technologies, microelectronics, such directions as telemedicine, digital health care, mobile medicine, 3D printing (additive technologies) and others have emerged. At the same time, without laboratory and instrumental studies, it becomes impossible not only to make a clinical diagnosis, but also to control the safety of treatment. The doctor's decision-making about diagnosis, prevention and treatment of the patient depends on the level of reliability of the research. Material and methods. The development of the theory and practice of application of technologies of diagnostics and treatment of diseases of internal organs, including informational ones is analyzed by methods of expert assessment. Unified modern technologies of clinical laboratory and radiological research methods that help improve the quality of care; methods of radiation therapy that increase the effectiveness of treatment of cancer and non-cancer diseases, as well as methods of decision-making in the diagnosis, treatment and prognosis of the patient's condition. Results. A modern idea of the training program for future specialists of the degree of Doctor of Philosophy in the specialty 224 "Technologies of medical diagnosis and treatment" (according to the international classification 0914 "Medical diagnostic and treatment technology") of the branch of knowledge 22 "Health care" is presented. Upon completion of their studies, third-level higher education students must master general scientific (philosophical) competencies, acquire universal research skills and language competencies. The topics of the training courses are designed to promote the ability to integrate knowledge and solve complex problems in multidisciplinary and transdisciplinary contexts. Conclusion. The content of the proposed educational-scientific program in specialty 224 "Technologies of medical diagnostics and treatment" is aimed at training highly qualified and competitive specialists of the degree of Doctor of Philosophy, acquisition by them in the course of training of necessary theoretical knowledge and a complex of practical abilities, skills and competences to perform innovative research, also the implementation of the obtained results in practical health care.